Role of platelet counts to spleen length ratio and platelet-albumin to spleen length ratio as non-invasive predictors of esophageal varices in chronic liver disease patients: A cross-sectional study in Eastern India - Y Sudheer Varma; Vijay Kumar; Ratnadeep Biswas; Vishnu Shankar Ojha; Divendu Bhushan; Ramesh Kumar; Rajeev Nayan Priyadarshi (Journal of Family Medicine and Primary Care)
Objective: This study aimed to evaluate and compare the diagnostic performance of the Platelet/Spleen Length (P/SL) ratio and a novel metric, the Platelet-Albumin/Spleen Length (P*Alb/SL) ratio, in predicting esophageal varices (EVs) among patients with chronic liver disease (CLD). Methods: A cross-sectional study was conducted over a period of 6 months, enrolling 121 newly diagnosed CLD patients without prior treatment for EV or CLD. Data collected, included demographic and clinical details, platelet count, serum albumin, and spleen length via ultrasonography. All patients underwent upper gastrointestinal endoscopy to assess EVs. The P/SL ratio was calculated by dividing platelet count (cells/μL) by spleen length (mm), and the Platelet-Albumin to Spleen Length (P*Alb/SL) ratio by dividing the product of platelet count and serum albumin (g/dL) by spleen length. Diagnostic performance was evaluated using receiver operating characteristic curve analysis and calculating sensitivity and specificity. Results: The P/SL ratio demonstrated an optimal cutoff of 856 with an area under the curve (AUC) of 0.924 (95% CI: 0.849–0.998), sensitivity of 92%, and specificity of 85.7%. The P*Alb/SL ratio had an optimal cutoff of 2194.5, achieving an AUC of 0.928 (95% CI: 0.864–0.992), sensitivity of 81%, and specificity of 95.2%. Both ratios exhibited strong diagnostic performance, with no significant difference between their AUCs (P = 0.712). The diagnostic odds ratios were 69 and 85.26 for the P/SL and P*Alb/SL ratios, respectively. Conclusion: The P/SL ratio proved to be an effective screening tool for EVs in CLD, with high sensitivity for early detection. The P*Alb/SL ratio showed similar or slightly superior diagnostic performance, with high specificity and fewer false positives, making it ideal for confirmation. Together, the sequential tandem use of P/SL followed by P*Alb/SL provides a practical strategy for risk stratification and patient management, while reducing reliance on the endoscopy and improving resource allocation, especially in resource-limited settings.